2013
DOI: 10.1155/2013/180137
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Orthodontic Brackets and Disinclusion Buttons: Effect of Water and Saliva Contamination

Abstract: Purpose. The aim of this study was to assess the effect of water and saliva contamination on the shear bond strength and failure site of orthodontic brackets and lingual buttons. Materials and Methods. 120 bovine permanent mandibular incisors were randomly divided into 6 groups of 20 specimens each. Both orthodontic brackets and disinclusion buttons were tested under three different enamel surface conditions: (a) dry, (b) water contamination, and (c) saliva contamination. Brackets and buttons were bonded to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Specimens were placed so that the bonded cylinder base was parallel to the shear force direction. Specimens were loaded at a crosshead speed of 1 mm/min [ 1 , 17 , 18 ] in an occluso-gingival direction. The maximum load necessary to debond the specimens was recorded in Newton (N) and then converted into MPa as a ratio of Newton to surface area of the cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were placed so that the bonded cylinder base was parallel to the shear force direction. Specimens were loaded at a crosshead speed of 1 mm/min [ 1 , 17 , 18 ] in an occluso-gingival direction. The maximum load necessary to debond the specimens was recorded in Newton (N) and then converted into MPa as a ratio of Newton to surface area of the cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred bovine permanent mandibular incisors were collected. After extraction, teeth were stored in a solution of 0.1% (weight/volume) thymol [ 11 ]. Inclusion criteria were no cracks, no caries, no rough or irregular buccal surface, and intact enamel [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently all specimens were then secured in the lower jaw of an universal testing machine (Model 3343, Instron, Canton, MA, USA) and then tested in shear mode (head speed: 1 mm/min) [ 11 ]. The bonding surface of the brackets remained perpendicular to the horizontal plane and parallel to the direction of the force to be applied, in an effort to minimize peel and maximize shear during testing [ 8 , 9 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Santos et al, [10] Sfondrini et al, and [11] Nirupama et al [12] concluded that water, saliva, and blood contamination of enamel during bonding procedures lowers the bond strength values.…”
Section: Discussionmentioning
confidence: 99%